2016
DOI: 10.1177/0961203316646462
|View full text |Cite
|
Sign up to set email alerts
|

Elevated plasma interleukin-37 levels in systemic lupus erythematosus patients

Abstract: This study aims to evaluate the plasma interleukin (IL)-37 levels in systemic lupus erythematosus (SLE) patients, as well as its association with major clinical and laboratory features. Ninety consecutively selected SLE patients and 78 community-based healthy controls were recruited. Plasma IL-37 levels were detected by enzyme-linked immunosorbent assay (ELISA). The major clinical and laboratory data of SLE patients were also recorded. The results showed that IL-37 level was significantly higher in the plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 14 publications
2
17
2
1
Order By: Relevance
“…Our results confirmed the findings of other studies where there were no statistically significant differences between IL‐37 level and musculoskeletal, hematological, CNS and serous membrane involvement ( P > 0.05) …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results confirmed the findings of other studies where there were no statistically significant differences between IL‐37 level and musculoskeletal, hematological, CNS and serous membrane involvement ( P > 0.05) …”
Section: Discussionsupporting
confidence: 92%
“…Contrasting our results were the findings of Wu et al ., who failed to find association between IL‐37 levels and SLE high disease activity and lupus nephritis. They attributed these differences to the different demographic characteristics, treatment modalities and sample size among different studies . Also, Godsell et al .…”
Section: Discussionmentioning
confidence: 99%
“…IL-37 gene expression in adipose tissue of humans was found to be higher in subjects with low adipose tissue leptin protein levels [15], which could suggest that high IL-37 expression lowers food intake and consequently reduces levels of the satiety hormone leptin in adipose tissue. Elevated IL-37 levels in humans are generally found in patients with inflammatory diseases such as nonallergic asthma [32] and systemic lupus erythematosus (SLE) [33]. SLE patients have indeed been reported to have inadequate food intake [34], which would be consistent with higher IL-37, but the complexity and versatility of the immune system makes it challenging to attribute this effect to a specific inflammatory component.…”
Section: Discussionmentioning
confidence: 99%
“…Wan et al reported that decreased IL-37 expression leads to the increased secretion of pro-inflammatory cytokines including IL-16 and IL-1β in degenerative intervertebraldisc, which suggests a function for IL-37 in delaying the progression of intervertebral disc degeneration (57). It has also been shown that IL-37 expression is significantly higher in the plasma of patients with SLE and that IL-37 suppresses the secretion of pro-inflammatory cytokines in PBMCs of SLE patients (60,73,74). IL-37b expression levels in serum and nasal lavage are significantly increased in children with allergic rhinitis (AR) (14).…”
Section: Chronic Inflammatory and Autoimmune Disordersmentioning
confidence: 99%